Direction Given Under the Legal Aid and Coroners' Courts Act (Northern Ireland) 2014 : Interim Payments in Cases Funded Under Article 12A of the Access to Justice (Northern Ireland) Order 2003.: Interim Payments in Cases Funded Under Article 12A of the Access to Justice (Northern Ireland) Order 2003. ([2017]) - Northern Ireland., Department of Justice
No abstract available